2007
DOI: 10.1007/s10853-007-1977-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional computer modeling of slag cement hydration

Abstract: A newly developed version of a three-dimensional computer model for simulating the hydration and microstructure development of slag cement pastes is presented in this study. It is based on a 3-D computer model for Portland cement hydration (CEMHYD3D) which was originally developed at NIST, taken over in the authors' group and further developed. Features like the digitized 3-D microstructure, the cellular automata (CA) algorithm for simulating the random walking, phase transformation for simulating the chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Similarly, Chen et al [23] also found that at the same curing age, the finer slag had a higher reaction degree than the coarser slag. Appl Figure 4 shows the parameter studies on the degree of binder reaction in the MK blended concrete.…”
Section: Reaction Of Cement-mk Blendsmentioning
confidence: 72%
See 2 more Smart Citations
“…Similarly, Chen et al [23] also found that at the same curing age, the finer slag had a higher reaction degree than the coarser slag. Appl Figure 4 shows the parameter studies on the degree of binder reaction in the MK blended concrete.…”
Section: Reaction Of Cement-mk Blendsmentioning
confidence: 72%
“…Similarly, Chen et al [23] also found that at the same curing age, the finer slag had a higher reaction degree than the coarser slag. …”
Section: Reaction Of Cement-mk Blendsmentioning
confidence: 72%
See 1 more Smart Citation
“…This model is primarily based on CEMHYD3D version 1.0 that was developed at NIST [3]. The UT model is modified from the original CEMHYD3D that simulates the processes of cement hydration and the formation of microstructure [18]. The UT version is an extension and can for instance simulate diffusion-controlled processes during cement hydration and minimize the influence of system resolution on the model predictions.…”
Section: Computer Simulationmentioning
confidence: 99%
“…A time conversion factor is used to relate the hydration cycles to real time. It is proven that the new CEMHYD3D UT version is robust in regard to the time conversion factor, indicating that most of the important kinetic factors of the cement hydration process are successfully considered in the computer model [18,19].…”
Section: Computer Simulationmentioning
confidence: 99%